Economic environmental dispatch of solar-wind-hydro-thermal power system. (September 2019) - Basu, M.
Highlights: EED is a significant chore in solar-wind-hydro-thermal power system. It is an extremely restricted multi-objective optimization problem. NSGA-II has been suggested for solving EED of solar-wind-hydro-thermal power system. Abstract : Economic environmental dispatch (EED) is a significant chore in solar-wind-hydro-thermal power system comprising multi-reservoir cascaded hydro plant with time delay, thermal plants with non-smooth fuel cost, NOx emission level and SO2 emission level functions, wind power generating units, solar PV plant and battery energy storage system. It is an extremely restricted multi-objective optimization problem linking conflicting objectives with both equality and inequality constraints. Here, non-dominated sorting genetic algorithm-II (NSGA-II) has been suggested for solving EED of solar-wind-hydro-thermal power system with battery energy storage system where generations are allocated among the on line units such that cost, NOx emission level and SO2 emission level are optimized simultaneously while fulfilling all operational constraints. Test results of two test systems acquired from the suggested technique have been fit to that acquired from strength pareto evolutionary algorithm 2 (SPEA 2).